Analysing generational transfer of brand loyalty in the dishwashing liquid product category, in the Western Cape Province - Coetzee, Quintin (School of Management Studies, 2020)
While the concept of brand loyalty is well-researched, qualitative studies pertaining specifically to generational transfer of brand loyalty in a South African fast-moving consumer goods context are few and far between. This study used the dishwashing liquid product category in the Western Cape Province of South Africa to analyse generational transfer of brand loyalty. Following a qualitative research methodology, using in-person interviews across two generations - children and parents/guardians - raw data was obtained. Participants were asked to provide information relating to their preferred brand of dishwashing liquid, as well as their reasons for using the brand, their loyalty towards the brand, as well as their likelihood of brand switching. The data underwent a thorough thematic data analysis. Codes, categories, and themes were identified, with the researcher continually seeking to identify patterns in responses. A number of findings were laid out, offering insights into the concept of generational transfer of brand loyalty, as well as a foundation for future research into the topic. The study established that, in the dishwashing liquid product category in the Western Cape, there is a strong degree of generational transfer of brand loyalty, and at times, the transfer has taken place across three generations. Aspects such as consumers’ use of a brand out of habit and brand associations also appear to transfer generationally at times. There is also a strong occurrence of brand loyalty in the product category - mostly towards Unilever’s Sunlight brand. Brand switching across generations is uncommon in this sector, prevented by factors including enthusiastic brand loyalty and budgetary limitations. When switching does occur, it is driven mainly by a desire to discover whether a better brand exists, and changes in price and availability. Price and effectiveness frequently combine to form assessments of value during consumers’ purchase decision process in this product category. This study provides insight into the phenomenon of generational transfer of brand loyalty, within the context of the FMCG industry in the Western Cape. The findings within may prove useful both to brand marketers as well as researchers seeking a foundation upon which to conduct further studies in this area. The implications of this study, and recommendations for future, related studies, have been discussed in this report.